Aiming for the Future: Transforming Social Studies Learning in Elementary School into the 21st Century - Hajaroh, Mami; Fauzi, Wildan Nuril Ahmad (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2023)
The purpose of social studies learning is for students to become sensitive to problems that arise both within themselves and in their social environment. Social studies learning must adapt to face the challenges of the 21st century, Social studies education has significant relevance to 21st century skills; 1) Global Understanding, 2) Critical Thinking Skills, 3) Communication Skills, 4) Problem-Solving Ability, 5) Global Citizenship, 6) Technology and Media Literacy and, 7) Collaboration Skills. Thus, social studies not only provides an understanding of historical facts and social reality, but also forms skills and attitudes that are in accordance with the demands of the changing world in the 21st century.